Effect of symbiont acquisition on growth, survival and fertility of the terrestrial isopod Porcellionides pruinosus (Crustacea, Oniscidea). Issue 1 (2nd January 2019) - Delhoumi, Majed; Zaabar, Wahiba; Bouslama, Mohamed Fadhel; Achouri, Mohamed Sghaier
ABSTRACT: Growth rate, survival, mean size of reproductive females and fertility were assessed in the terrestrial isopod Porcellionides pruinosus fed an artificial diet supplemented with potential sources of symbionts. The acquisition of symbionts was experimentally manipulated through feeding experiments to investigate the effect of the acquisition mechanism on isopod performances over 4 months. Five groups of isolated newborn were fed differently (basal diet or control; basal diet with leaf litter, faeces, gut; and basal diet mixed with antibiotic), weighed and counted at 0, 2 and 4 months. Growth rate differed significantly between diet groups at 2 and 4 months. No significant difference of survival was detected, but groups fed on a diet with supplements (leaf litter, faeces and gut) had a higher rate of survival. Size and fertility of reproductive females differed significantly across diet groups. Our findings showed the importance of the acquisition mode of symbionts on the life history of Oniscidea and the role of diet intake on the performance of P. pruinosus.